EVALUASI KONDISI LINGKUNGAN PERAIRAN KAWASAN PULAU ABANG, GALANG BARU, BATAM BERDASARKAN ANALISA INDEKS STORET DAN SIMILARITAS CANBERA - Sachoemar, Suhendar I (BPPT)
Evaluation of the water quality status at Abang Island Region was conducted by using the STORET and Canbera Similarity Indeks during Mei, June and October 2006. Thes analysis result shows that the water quality within this region was within the range of good to moderate. This condition indicats that the water quality status is still suitable to support the marine biotic life. During May, the water quality was good, but in June and October was decreased due to the increasing of the organic material transported by land surface run off driven by precipitation as response to the seasonal change.Key words : Kualitas air, Pulau Abang, Indeks Storet, Indeks Similaritas Canbera.